2010
DOI: 10.1039/c0sm00266f
|View full text |Cite
|
Sign up to set email alerts
|

Primary chondrocytes enhance cartilage tissue formation upon co-culture with a range of cell types

Abstract: Co-culture models have been increasingly used in tissue engineering applications to understand cell-cell interactions and consequently improve regenerative medicine strategies. Aiming at further elucidating cartilage tissue formation, we co-cultured bovine primary chondrocytes (BPCs) with human expanded chondrocytes (HECs), human dermal fibroblasts (HDFs), mouse embryonic stem cells (MESCs), or mouse-3T3 feeder cells (M3T3s) in micromasses. BPCs were either co-cultured (1 : 5 ratio) with all cell types allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…In the debate on the mechanisms behind the coculture-induced regeneration, there seems to have been a paradigm shift recently, based on evidence suggesting that MSCs, rather than differentiating, have trophic effects on chondrocytes (Fig. 1B) [46][47][48][49][50][51][52][53][54][55]. Nonetheless, regeneration may also result from both chondroinduction and MSC differentiation (Fig.…”
Section: Coculture-induced Tissue Regenerationmentioning
confidence: 99%
“…In the debate on the mechanisms behind the coculture-induced regeneration, there seems to have been a paradigm shift recently, based on evidence suggesting that MSCs, rather than differentiating, have trophic effects on chondrocytes (Fig. 1B) [46][47][48][49][50][51][52][53][54][55]. Nonetheless, regeneration may also result from both chondroinduction and MSC differentiation (Fig.…”
Section: Coculture-induced Tissue Regenerationmentioning
confidence: 99%
“…However, the beneficial effects of co-cultures for cartilage matrix formation was also found in a combination of chondrocytes and a variety of other cell types, such as adipose-tissue-derived stem cells, human embryonic stem cells, fibroblasts, and meniscus cells. [36][37][38][39] It is still unclear whether MSCs derived from adipose tissue or synovium have a comparable trophic role in the co-culture.…”
Section: Figmentioning
confidence: 99%
“…However, with the cellular interactions between MSCs and native chondrocytes receiving less attention [9], the molecular mechanism of interactions between MSCs and native chondrocytes is poorly understood [10]. In order to maximize the benefits of stem cell therapy, these cellular interactions need to be clarified.Previous reports showed that cartilage matrix formation was increased in co-cultures of human primary chondrocytes (hPCs) with MSCs compared with monocultures [11,12]. Further investigations revealed that the inductive effects of MSCs on cartilage formation were predominantly due to stimulation of hPCs proliferation in the co-culture pellets [13].…”
mentioning
confidence: 99%
“…Previous reports showed that cartilage matrix formation was increased in co-cultures of human primary chondrocytes (hPCs) with MSCs compared with monocultures [11,12]. Further investigations revealed that the inductive effects of MSCs on cartilage formation were predominantly due to stimulation of hPCs proliferation in the co-culture pellets [13].…”
mentioning
confidence: 99%